Modelling and neutron diffraction characterization of the interfacial bonding of spray formed dissimilar steels - Lee, TL; Mi, J; Ren, S; Zhao, S; Fan, J; Kabra, S; Zhang, S; Grant, PS (Elsevier, 2018)
The spray forming of thick, dissimilar steel clad tubes with the objective of achieving a high integrity metallurgical bond across the cladding-substrate interface able to withstand residual stresses and subsequent thermo-mechanical processing was investigated by large scale experiments, modelling and extensive microstructural characterization including microscopy, X-ray tomography, neutron scattering and mechanical testing. The simulated residual stress distributions across the cladding-substrate interface, accounting for any as-sprayed porosity and the distribution of martensitic and retained austenite phases, were compared with neutron diffraction measurements and differences used to infer the load transfer behaviour and thus the mechanical integrity of the interface. The mechanical properties of the interfaces were then also measured directly by shear testing. The link between substrate pre-heating, the spray forming temperature, and the resulting preform temperature, porosity, phase fractions, residual stress, strength and integrity of the interface were established and quantified explicitly.